Пьесы - Островский Александр Николаевич (Бриллиантовая коллекция, 2006)
Экземпляры: Ч.З. (20241217) / Инвентарный номер: 50700 / Цена: 200.00 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: О-77 / ББК: 84(2Рос=Рус)1